2022
DOI: 10.3390/nu14153021
|View full text |Cite
|
Sign up to set email alerts
|

Lower Serum Calcium Levels Associated with Disrupted Sleep and Rest–Activity Rhythm in Shift Workers

Abstract: Vitamin D deficiency is prevalent in many developed countries, and several studies suggest that vitamin D plays an essential role in brain function. A recent study showed that vitamin D deficiency was closely associated with daytime sleepiness and shorter sleep time. The relationshipbetween vitamin D levels and calcium levels is well established, and calcium level regulates slow-wave sleep generation. It is conceivable that the sleep disturbance in vitamin D deficiency may be due to an altered calcium level. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…This indicates that Ca 2+ -dependent neural hyperpolarization pathways are very closely related to slow-wave sleep. In a recent human study, shift workers with higher serum calcium concentrations tended to fall asleep more easily and have shorter total sleep times, whereas no such significant correlation was found in non-shift workers, and a negative correlation was found between the calcium concentration and peak time of daily activity as measured by actigraphy [ 55 ]. Therefore, the fact that increased calcium absorption appears at the beginning of the resting period may be an important physiological effect for better quality sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that Ca 2+ -dependent neural hyperpolarization pathways are very closely related to slow-wave sleep. In a recent human study, shift workers with higher serum calcium concentrations tended to fall asleep more easily and have shorter total sleep times, whereas no such significant correlation was found in non-shift workers, and a negative correlation was found between the calcium concentration and peak time of daily activity as measured by actigraphy [ 55 ]. Therefore, the fact that increased calcium absorption appears at the beginning of the resting period may be an important physiological effect for better quality sleep.…”
Section: Discussionmentioning
confidence: 99%
“…negative correlation was found between the calcium concentration and peak time of daily activity as measured by actigraphy [54]. Therefore, the fact that increased calcium absorption appears at the beginning of the resting period may be an important physiological effect for better quality sleep.…”
Section: Supplemental Figuresmentioning
confidence: 93%
“…The deficiencies are worldwide issues which are mainly associated with bone diseases [ 123 ]. Eventually, a recent study among shift workers showed that low serum calcium levels might be associated with circadian dysregulation as well as sleep disturbance [ 124 ]. Individuals with irregular sleep schedules may obtain less sun exposure, which contributes to vitamin D deficiency.…”
Section: Nutritional Strategies For Musculoskeletal Healthmentioning
confidence: 99%
“…A study conducted on shift workers found a link between low calcium levels and daytime dysfunction, sleep latency, and total sleep time. [34] According to recent studies, calcium is essential for producing slow oscillations during NREM sleep. [35] Low calcium levels may make it difficult for slow wave activity to be produced, necessitating longer sleep cycles to relieve the pressure associated with them during the wake phase.…”
Section: Vitaminmentioning
confidence: 99%
“…It is possible to assume that a low calcium level decreases slow-wave activity and lengthens total sleep time in order to preserve the homeostasis of slow-wave energy, which is the cumulative sum of slow-wave activity across total sleep duration. [34] The consumption of dairy products, which are high in tryptophan and calcium, has also been linked to reported improvements in sleep quality. Calcium facilitates the brain's use of tryptophan in the production of melatonin, enhancing sleep quality.…”
Section: Vitaminmentioning
confidence: 99%